Variations for physical and nutritional quality traits in advanced breeding lines of groundnut: Variations for physical and nutritional quality traits in advanced breeding lines of groundnut - PRAVEEN KONA,; M K MAHATMA,; K GANGADHARA,; NARENDRA KUMAR,; B C AJAY,; KIRTI RANI,; T RADHAKRISHNAN,; M C DAGLA,; LOKESH KUMAR, (Journal of Oilseeds Research, 2020)
Eighty four advanced breeding lines of groundnut were evaluated for quality traits with four checks during summer, 2019. Three genotypes, PBS 29180, PBS 29067 and PBS 29148 recorded 80.1 g, 76.3 g, and 72.6 g hundred kernel weight, respectively. Protein content was high (33.8%) in PBS 29124 followed by PBS 29082 (32.7%) and PBS 29116 (32.3%). The oil content ranged from 45.0% (PBS 29105) to 53.1 (PBS 19031). Soluble sugar content was high (6.95%) in PBS 29116. Three genotypes viz., PBS 29079B, PBS 29148 and PBS 29180 had desired combination of traits required for confectionery purpose which can be used as donor parents in breeding program or can be released as varieties after further evaluation and validation.